A teoria do objeto de Emil Lask - Resende Júnior, José de (2005)
The purpose of the present work is to introduce the object theory developed by Emil Lask in his Die Logik der Philosophie und die Kategorienlehre (1910). Even if such theory is not its goal, it works as auxiliary support in the attainment of book´s aim: to hold categorically the validity (Geltung) and save it from all hypostases forms, through that Lask deepens and transforms the value theory (Werttheorie) of Windelband and Rickert indeed under the critics of Husserl and the influence of the Lebensphilosophie. The present work will just expose and analyse the objectivity (Gegenständlichkeit) species developed by Lask, among which is included, for instance, objects as the tree, the green, the being, the beautiful, the ethical, the language and the numbers. In fact such objectivity is a sense theory completely independent of subjectivity